PPARγ activation attenuates neonatal CRD-induced visceral pain sensitization and anxiety in male rats by alleviating oxidative stress - Minjie Li; Xiyu Zhuo; Yongxiao Liu; Jinchao You; Jianqing Lin (BMC Gastroenterology)
Abstract Background Visceral pain sensitization and emotional reactions due to irritable bowel syndrome (IBS) occur frequently in the general population. Oxidative stress plays a crucial role in the pathogenesis of IBS. Previous studies have demonstrated that activation of peroxisome proliferator-activated receptor gamma (PPARγ) has analgesic effects. Therefore, we aimed to determine whether PPARγ activation ameliorates oxidative stress and affects thus nociceptive sensitization and emotional responses in IBS. Methods The study utilized male Sprague-Dawley (SD) rats, that suffered from neonatal colorectal distension (CRD), to assess the effects of various doses of rosiglitazone on visceral hyperalgesia and anxiety. Electromyography (EMG) of the external abdominal oblique muscles was used to evaluate visceral hypersensitivity, and Open Field Test (OFT) and Elevated Plus Maze (EPM) were used to evaluate anxiety. Superoxide dismutase (SOD) and malondialdehyde (MDA) in the spinal cord were analyzed by water-soluble tetrazolium-1 (WST-1) and thiobarbituric acid (TBA) methods, respectively, the expression levels of PPARγ in the spinal cord were assessed by qRT-PCR and Western blotting. Results Neonatal CRD-induced rats showed visceral pain sensitization and anxiety in adulthood, with down-regulated expression of PPARγ and SOD and elevated MDA levels in the spinal cord. Rosiglitazone alleviated visceral hypersensitivity and anxiety by activating PPARγ protein expression and promoting MDA up-regulation and SOD down-regulation in the spinal cord, which were reversed by GW9662, an antagonist of PPARγ. Conclusion This study demonstrated that rosiglitazone alleviated visceral pain sensitization and anxiety in male IBS rats by alleviating oxidative stress through activation of PPARγ.